2010
DOI: 10.1111/j.1469-8749.2010.03819.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intensity of participation in leisure and recreational activities by children with cerebral palsy

Abstract: AIM To test a model of child, family, and service determinants of intensity of participation in leisure and recreational activities by children with cerebral palsy (CP).METHOD Participants were 288 children with CP, age range 6 to 12 years (mean 9y 8mo, SD 2y), and their parents from seven children's hospitals. The sample comprised 166 (57.6%) males and 122 (42.4%) females, and between 40 (13.9%) and 74 (25.7%) children in each of the five levels of the Gross Motor Function Classification System. Children comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
3
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 27 publications
4
84
3
6
Order By: Relevance
“…Children with higher physical ability had fewer activity limitations and participation restrictions than those with lower physical ability (Palisano et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…Children with higher physical ability had fewer activity limitations and participation restrictions than those with lower physical ability (Palisano et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…Even though the inclusion criteria were comparable in all three countries, a limitation is that we cannot know if the children's functional levels, were equivalent. Studies of children with CP have reported that a lower level of functioning is correlated with lower participation level [17,20,23,27]. There are studies indicating that type of disability is of less importance for the pattern of participation than severity of impairment [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Children with disabilities often meet restrictions in their participation due to both personal and environmental factors [5,[15][16][17][18][19][20]. Pain, mobility problems, communication disorders, and intellectual disabilities are examples that can reduce participation [17,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The CAPE generates knowledge on contextual factors and the experience of participation, The literature appears to agree that if an activity is going to be experienced as meaningful and engaging over time, it has to be enjoyable and self-initiated (Hammel et al, 2008;Heah et al, 2007;King et al, 2009;Palisano et al, 2010b). Children's interests are of great importance for participation in leisure activities in general, and in physical activity specifically, and should be seriously considered in rehabilitation interventions.…”
Section: Preferences and Enjoymentmentioning
confidence: 99%